2021
DOI: 10.7717/peerj.10671
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing analysis of FGF2-responsive transcriptome in skin fibroblasts

Abstract: Background Fibroblast growth factor 2 (FGF2) is a highly pleiotropic cytokine with antifibrotic activity in wound healing. During the process of wound healing and fibrosis, fibroblasts are the key players. Although accumulating evidence has suggested the antagonistic effects of FGF2 in the activation process of fibroblasts, the mechanisms by which FGF2 hinders the fibroblast activation remains incompletely understood. This study aimed to identify the key genes and their regulatory networks in sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
2
1
0
Order By: Relevance
“…In addition, the underlying mechanisms for causing some additive effect by FGF-2 and TGF-β2 as observed in the biophysical analyses of the above 2D and 3D HconF cells remain to be elucidated despite our efforts to closely examine the several candidate molecules. Therefore, to better understand the results related to the role of FGF-2 on TGF-β2-induced fibrogenetic changes of 2D and 3D cultured HconF cells, further investigations, including an RNA-Seq experiment will be needed to elucidate possible mechanisms linked with several other complex signaling networks in order to confirm our present observations, since quite recently, in an RNA-Seq study, the FGF-2-responsive transcriptional profile was comprehensively analyzed and the findings revealed potential candidates for mechanisms in terms of FGF-2-mediated wound healing using skin fibroblasts 56 .…”
Section: Discussionsupporting
confidence: 65%
“…In addition, the underlying mechanisms for causing some additive effect by FGF-2 and TGF-β2 as observed in the biophysical analyses of the above 2D and 3D HconF cells remain to be elucidated despite our efforts to closely examine the several candidate molecules. Therefore, to better understand the results related to the role of FGF-2 on TGF-β2-induced fibrogenetic changes of 2D and 3D cultured HconF cells, further investigations, including an RNA-Seq experiment will be needed to elucidate possible mechanisms linked with several other complex signaling networks in order to confirm our present observations, since quite recently, in an RNA-Seq study, the FGF-2-responsive transcriptional profile was comprehensively analyzed and the findings revealed potential candidates for mechanisms in terms of FGF-2-mediated wound healing using skin fibroblasts 56 .…”
Section: Discussionsupporting
confidence: 65%
“…File 2). Of note, among these, the most activated genes in our study ESM-1 and MMP-1 are also found in other studies reporting FGF2-induced genes 32,33 . Activation of three of those four genes by FGF2-EVs was confirmed by RT-qPCR in DFs (Fig.…”
Section: Resultssupporting
confidence: 89%
“…RNA sequencing technique had been utilized to investigate the effects of FGF2 on mRNA transcription in fibroblasts derived from the skin and lung ( Fortier et al, 2021 ; Kashpur et al, 2013 ; Wu et al, 2021a ). As described, the expression of cytoskeleton genes and ECM organization genes, e.g ., Acta2 , Myh10 , Eln , Col1a1 , Col1a2 and Postn , was significantly decreased, which is consistent with our findings ( Fortier et al, 2021 ; Kashpur et al, 2013 ; Wu et al, 2021a ). Nevertheless, fibroblasts isolated from different tissues exhibit certain heterogeneity, which may result in the diversity of gene expression regulated by FGF2.…”
Section: Discussionmentioning
confidence: 99%